Recruiting and Retaining America's Finest Evidence-Based Lessons for Police Workforce Planning - Wilson, Jeremy M. (RAND Corporation, 2010)
Shares results of a survey, sent to every U.S. police agency with at least 300 sworn officers, on recruitment and retention practices. Finds that police compensation, city size, and crime rates affected recruiting. Advertising and incentives had little effect on the number of recruits. Cohort sizes highlighted management challenges. To facilitate comparative and longitudinal staffing analyses, ongoing national data collection is recommended.